PENGARUH KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA THE COFFEE SHOP JL.KETINTANG NO.73 SURABAYA - SULISTIANINGRUM, DIAH (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
High mobility urban communities resulting in a shift in consumption patterns that become fulfillment activities to achieve satisfaction to prestige . This led to the growing business in the field of Food Service, which not only puts the quality of the product but also the quality of services in accordance with customer expectations . This study aims to determine the effect of service quality on purchase decisions in the coffee shop kofisyop Tembalang . Where the independent variables are tangible / intangible ( X1 ) , Emphaty / Empathy ( X2 ) , Reliability / Reliability ( X3 ) , Responsiveness / response ( X4 ) , and Assurance / guarantee ( X5 ) and the dependent variable is the purchase decision ( Y ) . Based on statistical data analysis , the indicators in this study are valid and reliabel. Result of regression variables showed that simultaneous service quality significantly influence purchasing decisions , the value of F at 27.799 . In the classical assumption test , regression models multikolonieritas free , heterosdastisitas not happen , and the normal distribution . Partially , the variable that has the most impact is variable assurance with a regression coefficient of 0.274 . Figures Adjusted R Square of 0.450 = 45 % indicates that the variable purchase decisions can be explained by service quality variable such as tangible , Empathy , Reliability , response ( X4 ) , and Assurance ( X5 ) while the remaining 55 % is explained by other variables outside of the five variables used in the study this . Keyword: Service Quality,Purchasing Decision